Green Synthesis and Applications of ZnO and TiO2 Nanostructures - Gonçalves, Rosana A. [UNESP]; Toledo, Rosimara P. [UNESP]; Joshi, Nirav; Berengue, Olivia M. [UNESP] (MDPI, 2021)
Over the last two decades, oxide nanostructures have been continuously evaluated and used in many technological applications. The advancement of the controlled synthesis approach to design desired morphology is a fundamental key to the discipline of material science and nanotechnology. These nanostructures can be prepared via different physical and chemical methods; however, a green and ecofriendly synthesis approach is a promising way to produce these nanostructures with desired properties with less risk of hazardous chemicals. In this regard, ZnO and TiO2 nanostructures are prominent candidates for various applications. Moreover, they are more efficient, non-toxic, and cost-effective. This review mainly focuses on the recent state-of-the-art advancements in the green synthesis approach for ZnO and TiO2 nanostructures and their applications. The first section summarizes the green synthesis approach to synthesize ZnO and TiO2 nanostructures via different routes such as solvothermal, hydrothermal, co-precipitation, and sol-gel using biological systems that are based on the principles of green chemistry. The second section demonstrates the application of ZnO and TiO2 nanostructures. The review also discusses the problems and future perspectives of green synthesis methods and the related issues posed and overlooked by the scientific community on the green approach to nanostructure oxides.
Keywords: green synthesis; industrial applications; metal oxide nanostructures; TiO2; ZnO